Italy and Mozambique: science, economy and society within a history of an anomalous cooperation - Bussotti, L.; Muti, A. (Advances in Historical Studies, 2013)
In this article the authors aim at showing how an “anomalous” international and very intense cooperation between Italy and Mozambique was born. In fact, Italy has not a strong colonial tradition, especially in Mozambique, so it seems interesting to try to understand the reason why this former Portuguese colony has become the Italian most important partner in its cooperation activity. This analysis is based on the main hypothesis related to the birth of international bilateral cooperation: they have been seriously considered in order to explain the origin of this strange relationship, but they cannot completely clarify this particular case. According to the Italian social and political recent history, the privileged relationship with Mozambique is due more to a “bottom up” process than to geo-strategic or economic reasons. The fact that Mozambique had belonged to a weak Western power such as Portugal certainly gave Italy the opportunity to penetrate more easily in this country than in the ones which had been under the strong dominion of France or England. One of the most important results of this “anomalous” cooperation has to be found in the scientific fields (such as geology, architecture, biotechnologies) and in its impact on the development of Mozambique.